Self-assembly and anion recognition with binuclear lanthanide complexes - Thom, J; James Thom (2014)
This work describes an investigation into the solution-phase binding of anionic guests by bimacrocyclic lanthanide complexes. It outlines the preparation of different classes of complexes bearing two metallic domains, and the effects of association on both the complex and the guest. Chapter one provides a cursory introduction to the fundamental properties of the lanthanides with a focus on luminescence. A brief literature review is given on the use of emissive lanthanide probes for the sensing of analytes. Chapter two concerns the preparation and properties of a series of binuclear complexes in which the two centres are linked with a short spacer group, with the aim of selectively sequestering small anions such as the halides in solution. The concept of luminescence titration will be introduced and then used to assess the binding parameters of a selection of guests. Chapter three describes a related class of ditopic lanthanide complexes in which the two metal centres are separated by a semi-rigid butyne linking group. Luminescence studies are again used to evaluate the binding constants of homologous series of dianions to ascertain how the size, geometry and functionalization of the anionic guest impacts on binding. Chapter four explores the coordination of phosphate species and assesses the ability to bind biologically significant phosphates of some of the complexes from Chapter 3. Chapter five details an investigation into the effects on guest-selectivity of further lengthening the linking unit which separates the two macrocyclic binding domains. Chapter six summarises the work done throughout the thesis and draws some overarching conclusions, as well as highlighting areas for further study. Chapter seven describes the experimental procedures.